Monitoring Unusual Activity Using Remote-Controlled Computer and Android Based Application - Chitra, Batumalai; Raheel, Jilani; Malathy, Batumalay (INTI International University, 2019)
Monitoring activities using remote controlled computer, is an application that can control the computer’s functionality remotely from an android based application. The system consisted of the software using Eclipse to generate an automated number to add the computer onto the android application. Users can add computer through this software where the added computer will be linked and the android based application will be able to identify how many PC’s are connected. The second part is an Android based application using Android Studio to develop and follow up action. The integration between these two programs using Firebase to “Push” the information, to “Get” the information and to “Set” the information from one program to the other. The system can control different application of the computer upon linked to the android application, there is no need of other hardware, having a good connection of internet will be sufficient to carry out this application function. The system is suitable for cyber cafe and clients who want to monitor user’s activity remotely.